Exploration of the HIF-1α/p300 interface using peptide and Adhiron phage display technologies1. Issue 10 (15th October 2015) - Kyle, Hannah F.; Wickson, Kate F.; Stott, Jonathan; Burslem, George M.; Breeze, Alexander L.; Tiede, Christian; Tomlinson, Darren C.; Warriner, Stuart L.; Nelson, Adam; Wilson, Andrew J.; Edwards, Thomas A.
<x xml:space="preserve">Abstract</x> A range of experimental approaches are used to understand the HIF-1α/p300 interface – an important anticancer drug development target – in greater detail.